Community Planning: Fostering Participation in the Congested State? - Cowell, Richard (Local Government Studies)
The proliferation of partnership working across the British state raises difficult questions for democratic control and public participation. It is widely anticipated that 'community plans' - comprehensive strategies to promote social well-being - will address these issues, by facilitating public involvement in the governance of local areas. This paper examines community planning in Scotland to assess how far this hope is justified, drawing on government-sponsored research and a case study of community planning conferences. While community planning is extending opportunities for involvement, democratising local governance is subservient to dominant concerns with promoting joint working and demonstrating added value. Participatory events are structured to sustain belief in these activities.